PENELITIAN LANJUTAN PENINGKATAN KESEIMBANGAN LANSIA DENGAN PEMBERIAN LATIHAN BERDIRI SATU KAKI DAN LATIHAN ANKLE STRATEGY - Ivanali, Kesit; Ramadhona, Shella; Mailani, Rena (Universitas Pembangunan Nasional Veteran Jakarta, 2025)
Background: Balance in the elderly declines with age, increasing the risk of falls. Exercises such as single leg stance and ankle strategy exercise can help, but their effectiveness needs further investigation. Comparing the effects of latihan berdiri satu kaki and latihan strategi ankle on balance improvement in the elderly. Methods: This quasi-experimental study used a pretest-posttest group design involving 20 elderly participants from Panti Werdha Wisma Mulia, divided into two groups (10 participants each). The first group performed single leg stance, while the second group performed ankle strategy exercise. Balance was measured using the Functional Reach Test (FRT). Results: Single leg stance significantly improved balance (p ≤ 0.001), with a mean ± SD increase from 10.20 ± 2.394 to 12.80 ± 3.120. Ankle strategy exercise was more effective (p ≤ 0.001), increasing balance from 12.00 ± 3.590 to 19.20 ± 4.517. Independent T-test showed a significant difference (p = 0.001), with ankle strategy exercise having a greater effect. Conclusion: Ankle strategy exercise is more effective than single leg stance in improving balance in the elderly and can serve as a better intervention to reduce the risk of falls. Keywords: Single Leg Stance; Ankle Strategy Exercise; Balance; Functional Reach Test